Effect of the Programmed Nutrition Beef Program on moisture retention of cooked ground beef patties and enhanced strip loins - Phelps, K. J.; Drouillard, James S.; Jennings, J. S.; Depenbusch, B. E.; Vaughn, M. A.; Burnett, Derris D.; Ebarb, S. M.; Dietz, G. J.; Heitschmidt, J. D.; Noel, J. A.; Houser, Terry A.; Gonzalez, John M. (My University, 2015)
This study evaluated the influence of the Programmed Nutrition Beef Program and exogenous growth promotants (ExGP) on water holding capacity characteristics of enhanced beef strip loins. Sixty, frozen strip loins, arranged in a 2 × 2 factorial treatment arrangement with dietary program serving as the first factor and use of ExGP as the second factor, were thawed, injected with an enhancement solution, and stored for 7 days. Loins from ExGP cattle possessed the ability to bind more (P < 0.05) water before pumping and bind less (P < 0.05) water after pumping and storage. Loin pH across treatments was similar (P > 0.10) before injection, but increased post-injection and after storage (P < 0.01). Treatments did not affect loin purge loss, steak cook loss, and expressible moisture (P > 0.10). The Programmed Nutrition Beef Program and use of ExGPs minimally impacted water holding capacity of enhanced frozen/thawed beef strip loins.
Keywords: Water-holding; Beef; Ractopamine; Feeding; Enhancement